Penerapan Model Pembelajaran Kooperatif Tipe NHT( Numbered Heads Together ) Pada Materi Polinomial Untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa Kelas XI MS 4 SMA Negeri 1 Narmada Tahun Ajaran 2018/2019 - Fitraturrahman; Harry Soeprianto; Junaidi; Sripatmi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The research aimed to improve activity and learning achievement of the students on Polynomial learning at class XI MS 4 SMA Negeri 1 Narmada in academic year 2018/2019 by application of cooperative learing type Numbered Heads Together. The type of this research was a classroom action researc was conducted in two cycles. Each cycle contained planning, implementation, observation, evaluation, and reflection. The result showed that the activity score of students in cycle I meeting one is 8 with the least active category and meeting dua is 11.99 with active categories, in cycle II meeting one is 13.33 with the category of activity and meeting two which is 14,66 with a very active category. For the average value of student learning achievement in cycle I, cycle II, it was 69.67 and 78.70 with classical completeness respectively 60.00%, and 92.50%. It can be concluded that this researchby application of cooperative learning type Numbered Heads Together can improve the activity and learning achievement on Polynomial learning at class XI MS 4 SMA Negeri 1 Narmada in academic year 2018/2019.